Računski model za opis temperaturnega vpliva na meritve deformacij - Bohinc, Uroš (Gradbeni vestnik, 2022)
The paper presents an original method for predicting the dependence of measured deformations on ambient temperature. It is derived from a physical model calibrated using a set of existing measurements covering the time span of one year. The aim of the structural health monitoring of the bell tower of the Cathedral of St. Anastasia in Zadar was to reliably determine any long-term trends in behavior and thus enable timely planning of interventions. Separating the effects of temperature on measurements is key to successfully determining long-term trends. The results show that the temperature influence on the measurements can be eliminated well in the presented way.
Keywords: deformacije; konstrukcije; meritve; modeliranje temperaturnega vpliva; spremljanje konstrukcijskega stanja